Concepção e desenvolvimento de uma formação continuada de professores de matemática baseado na sequência Fedathi - Pinheiro, Ana Cláudia Mendonça (2016)
Teacher education is an issue transversed by several dilemmas. Discussion and research on continuing teacher education have mobilized reflections on the dimensions of teacher professional development and different understandings have been presented. In our experience and discussions, we attempt to understand how teachers of Mathematics rebuilding their teaching practices from studies, interactions and educational monitoring. Broadening our studies, we found out the need for a continuing education design specific for math teacher of elementary school. Bringing together difficulties both in teachers´ practice and in math language, has given rise to think about organizing an education methodology that articulate theory and practice to improve teaching skills based on Fedathi Sequence to mediate the formation of concepts. From this initial idea, some questions guided the discussion: What are the pedagogical basis for a continuing education methodology for math teachers in-service? What lecture design is suited to such methodology considering the characteristics of the target audience? Which are the appropriate guidelines for the math teachers and students formation on theoretical and didactic concepts, based on Fedathi Sequence? This study sought for answers to these questions through the design of a pedagogical methodology for continuing math teacher education in-service at elementary school. This study is justified by the importance of investigating a continuing education model to work with the guidance of training of school mathematics teachers taking for granted his performance in service and its upgrade needs, reframing and exchange experiences with their natural peers entered a same community.